SISTEM PAKAR UNTUK MENDIAGNOSA AWAL JENISGANGGUAN TIDUR BERBASIS WEB MENGGUNAKANMETODE DEMPSTER SHAFER - Buyung Habi Sazali, (2021)
A sleep disorder is a disorder that affects, interferes with, or involves sleep. A person who has a sleep disorder usually thinks this is normal and usually someone who has a sleep disorder goes to a psychiatrist for consultation. This system is expected to be able to assist psychiatrists in diagnosing types of sleep disorders quickly and efficiently. This expert system uses the Dempster Shafer method which functions to process the symptoms felt by the individual and produces the types of sleep disturbances experienced based on the symptoms that have been processed. The design of this system uses a variety of programming languages such as PHP, HTML, and CSS. This system produces an initial diagnosis of sleep disorders in accordance with the calculation of the Dempster Shafer method and produces an initial solution for handling each type of sleep disorder.